TIMolol Nasal Spray as a Treatment for Epistaxis in Hereditary Hemorrhagic Telangiectasia (TIM-HHT)-A Prospective, Randomized, Double-Blind, Controlled, Cross-Over Trial - Kornelia E. C. Andorfer; Florian Zeman; Michael Koller; Judith Zeller; René Fischer; Caroline T. Seebauer; Veronika Vielsmeier; Christopher Bohr; Thomas S. Kühnel (MDPI AG, 2022)
To date, there is no approved local therapeutic agent for the treatment of epistaxis due to hereditary hemorrhagic telangiectasia (HHT). Several case reports suggest the topical use of timolol. This monocentric, prospective, randomized, placebo-controlled, double-blinded, cross-over study investigated whether the effectiveness of the standard treatment with a pulsed diode laser can be increased by also using timolol nasal spray. The primary outcome was severity of epistaxis after three months, while the main secondary outcome was severity of epistaxis and subjective satisfaction after one month. Twenty patients were allocated and treated, of which 18 patients completed both 3-month treatment sequences. Timolol was well tolerated by all patients. Epistaxis Severity Score after three months, the primary outcome measure, showed a beneficial, but statistically nonsignificant (p = 0.084), effect of additional timolol application. Epistaxis Severity Score (p = 0.010) and patients' satisfaction with their nosebleeds after one month (p = 0.050) showed statistically significant benefits. This placebo-controlled, randomized trial provides some evidence that timolol nasal spray positively impacts epistaxis severity and subjective satisfaction in HHT patients when additively applied to standard laser therapy after one month. However, the effect of timolol was observed to diminish over time. Trials with larger sample sizes are warranted to confirm these findings.